“In Heavy Chains”: The Treatment of Prisoners of War in the Teutonic Order in Prussia, the Kingdom of Poland and the Grand Duchy of Lithuania in the First Half of the Fifteenth Century - Antanas Petrilionis (Lietuvos Istorijos Studijos)
This article delves into a analysis of the treatment of prisoners of war during the late 14th and 15th centuries. The study not only examines the challenges encountered by the prisoners themselves, as documented in their letters, but also sheds light on the difficulties faced by the officials of the Teutonic Knights and lords involved in their release and care. The work highlights the most salient aspects of captivity, including the deprivation experienced by the prisoners, the means by which they were able to obtain basic necessities such as food and clothing, and the types of places in which they were typically detained. Moreover, the article explores the various factors that influenced the behavior of both captors and captives, and distinguishes between the appropriate and inappropriate treatment of prisoners based on the established norms of medieval times.